2018
DOI: 10.3390/nu10010095
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Flavonoids and Ventilatory Function in European Adults: A GA2LEN Study

Abstract: Background: Flavonoids exert anti-inflammatory properties and modulate oxidative stress in vitro, suggesting a protective effect on lung function, but epidemiological studies examining this association are scarce. Methods: A stratified random sample was drawn from the GA2LEN screening survey, in which 55,000 adults aged 15 to 75 answered a questionnaire on respiratory symptoms. Post-bronchodilator spirometry was obtained from 2850 subjects. Forced vital capacity (FVC), the ratio between the forced exhaled volu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…This is possibly a result of differences in the method of dietary assessments, as well as the use of the MSM to calculate usual daily intake from two repeated 24-h dietary recalls, it could also be as a result of difference/change in population characteristics. Our analysis indicates that the Australian population consumes intermediate quantities of anthocyanins compared to other populations (Table 4), although with quantities similar to estimates from some European countries including Belgium, Norway, Sweden and Denmark (57,58) . A need for tailored databases for nutritional epidemiological studies cannot be overemphasised.…”
Section: Discussionsupporting
confidence: 70%
“…This is possibly a result of differences in the method of dietary assessments, as well as the use of the MSM to calculate usual daily intake from two repeated 24-h dietary recalls, it could also be as a result of difference/change in population characteristics. Our analysis indicates that the Australian population consumes intermediate quantities of anthocyanins compared to other populations (Table 4), although with quantities similar to estimates from some European countries including Belgium, Norway, Sweden and Denmark (57,58) . A need for tailored databases for nutritional epidemiological studies cannot be overemphasised.…”
Section: Discussionsupporting
confidence: 70%
“…Anthocyanin intake was found to have a strong protective effect against age-related lung function decline in a longitudinal study among elderly men [ 70 ]. Dietary intake of total flavonoids, catechins, and pro-anthocyanidins was shown to have an inverse relationship with lung function decline in several cross-sectional studies [ 68 , 71 ].…”
Section: Nutrients and Phytochemicals Against Lung Function Attenumentioning
confidence: 99%
“…This Special Issue “Effects of Polyphenol-Rich Foods on Human Health” comprises 64 peer-reviewed papers, including 43 original research papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], one case-report [ 51 ] and 20 literature reviews [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
mentioning
confidence: 99%
“…Epidemiological and clinical studies reported the following associations of polyphenols and polyphenol food extracts: silibinin and non-alcoholic fatty liver disease [ 9 , 39 ], resveratrol and hepatic encephalopathy [ 33 ], coffee polyphenols and cardiovascular risk factors [ 34 ], flavonoids and ventilator function [ 20 ], tea and stress and sleep quality (depending on caffeine content) [ 46 ], tea and glycemic response [ 44 ], polyphenols and obesity [ 24 ], phenolic acids and hypertension [ 22 ], healthy diet and neurofibromatosis [ 51 ].…”
mentioning
confidence: 99%